Stream of Consciousness in the under-discussion Urdu Novel - Hassan, Amer (sourcecoder, 2022)
In the view of critics, the term "stream of consciousness" was first used by American man of letters and psychologist William James. It has been used extensively in the novel. It is also being used in short stories quite widely these days. The Europeans think that "stream of consciousness" was used by Doerthy Richardson and Virginia Woolf to adorn their novels. James Joyce gave climax to this technique. In Urdu novel, Sajjad Zaheer was the first to use stream of consciousness in his novel “London ki Aik Raat". After him Aziz ahmad, Qurat ul Ain Haider, Karshan Chandar,Anwer Sajaad and Joginder Pual used this technique in their novels